A light-weight compact proton gantry design with a novel dose delivery system for broad-energetic laser-accelerated beams. (13th June 2017) - Masood, U; Cowan, T E; Enghardt, W; Hofmann, K M; Karsch, L; Kroll, F; Schramm, U; Wilkens, J J; Pawelke, J
Abstract: Proton beams may provide superior dose-conformity in radiation therapy. However, the large sizes and costs limit the widespread use of proton therapy (PT). The recent progress in proton acceleration via high-power laser systems has made it a compelling alternative to conventional accelerators, as it could potentially reduce the overall size and cost of the PT facilities. However, the laser-accelerated beams exhibit different characteristics than conventionally accelerated beams, i.e. very intense proton bunches with large divergences and broad-energy spectra. For the application of laser-driven beams in PT, new solutions for beam transport, such as beam capture, integrated energy selection, beam shaping and delivery systems are required due to the specific beam parameters. The generation of these beams are limited by the low repetition rate of high-power lasers and this limitation would require alternative solutions for tumour irradiation which can efficiently utilize the available high proton fluence and broad-energy spectra per proton bunch to keep treatment times short. This demands new dose delivery system and irradiation field formation schemes. In this paper, we present a multi-functional light-weight and compact proton gantry design for laser-driven sources based on iron-less pulsed high-field magnets. This achromatic design includes improved beam capturing and energy selection systems, with a novel beam shaping and dose delivery system, so-called ELPIS. ELPIS system utilizes magnetic fields, instead of physical scatterers, for broadening the spot-size of broad-energetic beams while capable of simultaneously scanning them in lateral directions. To investigate the clinical feasibility of this gantry design, we conducted a treatment planning study with a 3D treatment planning system augmented for the pulsed beams with optimizable broad-energetic widths and selectable beam spot sizes. High quality treatment plans could be achieved with such unconventional beam parameters, deliverable via the presented gantry and ELPIS dose delivery system. The conventional PT gantries are huge and require large space for the gantry to rotate the beam around the patient, which could be reduced up to 4 times with the presented pulse powered gantry system. The further developments in the next generation petawatt laser systems and laser-targets are crucial to reach higher proton energies. However, if proton energies required for therapy applications are reached it could be possible in future to reduce the footprint of the PT facilities, without compromising on clinical standards.